2014
DOI: 10.1089/neu.2013.3040
|View full text |Cite
|
Sign up to set email alerts
|

Acute Biomarkers of Traumatic Brain Injury: Relationship between Plasma Levels of Ubiquitin C-Terminal Hydrolase-L1 and Glial Fibrillary Acidic Protein

Abstract: Biomarkers are important for accurate diagnosis of complex disorders such as traumatic brain injury (TBI). For a complex and multifaceted condition such as TBI, it is likely that a single biomarker will not reflect the full spectrum of the response of brain tissue to injury. Ubiquitin C-terminal hydrolase L1 (UCH-L1) and glial fibrillary acidic protein (GFAP) are among of the most widely studied biomarkers for TBI. Because UCH-L1 and GFAP measure distinct molecular events, we hypothesized that analysis of both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
308
2
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 366 publications
(352 citation statements)
references
References 23 publications
16
308
2
4
Order By: Relevance
“…26,39 While the number of plasma samples is still relatively small within the cohort, the TRACK-TBI pilot dataset was selected for this study because it is well-characterized with 13 published articles regarding various components of these TBI patients across the full range of TBI severity-including proteomic and genetic biomarkers, neuroimaging, and outcome data. 31,36,37,[40][41][42][43] Based on the 217 subjects with available biosamples from this cohort, we identified that anti-GFAP autoantibody levels were elevated in acute plasma samples from brain injury subjects who had a self-reported history of previous TBI with or without LOC when compared with patients with acute TBI without self-reported previous TBI (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26,39 While the number of plasma samples is still relatively small within the cohort, the TRACK-TBI pilot dataset was selected for this study because it is well-characterized with 13 published articles regarding various components of these TBI patients across the full range of TBI severity-including proteomic and genetic biomarkers, neuroimaging, and outcome data. 31,36,37,[40][41][42][43] Based on the 217 subjects with available biosamples from this cohort, we identified that anti-GFAP autoantibody levels were elevated in acute plasma samples from brain injury subjects who had a self-reported history of previous TBI with or without LOC when compared with patients with acute TBI without self-reported previous TBI (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…1,36,37 Of 586 subjects with acute TBI from the TRACK-TBI pilot, we identified 196 with available acute plasma samples (collected within 24 h of injury) for this autoantibody study. Study patients covered the range of initial GCS of 3-15, which are reported with age, sex, and admission head CT distributions in Table 1.…”
Section: Anti-gfap Autoantibody Levels In Acute Plasma Samples From Tmentioning
confidence: 99%
“…Glial fibrillary acid protein (GFAP), 10,11 microtubule-associated protein tau, [12][13][14] and amyloid b peptide (particularly the 1-42 fragment, Ab42) 12 have been proposed as promising diagnostic and prognostic biomarkers in TBI. GFAP is a structural protein expressed almost exclusively in astrocytes and released upon disintegration of the cytoskeleton.…”
Section: Introductionmentioning
confidence: 99%
“…15 GFAP has been widely studied in TBI, and elevated levels in plasma show promise as a diagnostic and prognostic biomarker. 10,11 In moderate and severe TBI, GFAP levels are elevated in cerebrospinal fluid (CSF) and serum, particularly in patients who experienced an unfavorable outcome. 16 In addition, GFAP had excellent sensitivity to discriminate TBI patients from controls (with area under curve [AUC] 0.87) in the Transforming Research and Clinical Knowledge in TBI (TRACK-TBI) study in which 85% of the patient cohort had mild TBI.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, UCH-L1 has been reported to be a useful TBI biomarker in humans (72). Another study found that measuring serum UCHL-1 and GFAP levels improves the sensitivity and specificity of the diagnosis of TBI, since these biomarkers reflect different injury mechanisms (16). The same authors also found that UCHL-1 was poorly predictive of patient recovery and was better at predicting poor outcome.…”
Section: Introductionmentioning
confidence: 98%